Systematic review of antibiotic treatment for acute calculous cholecystitis. Issue 7 (30th March 2016) - van Dijk, A H; de Reuver, P R; Tasma, T N; van Dieren, S; Hugh, T J; Boermeester, M A
Abstract: Background: Intravenous antibiotics are frequently used in the initial management of acute calculous cholecystitis (ACC), although supportive care alone preceding delayed elective cholecystectomy may be sufficient. This systematic review assessed the success rate of antibiotics in the treatment of ACC. Methods: A systematic search of MEDLINE, Embase and Cochrane Library databases was performed. Primary outcomes were the need for emergency intervention and recurrence of ACC after initial non-operative management of ACC. Risk of bias was assessed. Pooled event rates were calculated using a random-effects model. Results: Twelve randomized trials, four prospective and ten retrospective studies were included. Only one trial including 84 patients compared treatment with antibiotics to that with no antibiotics; there was no significant difference between the two groups in terms of length of hospital stay and morbidity. Some 5830 patients with ACC were included, of whom 2997 had early cholecystectomy, 2791 received initial antibiotic treatment, and 42 were treated conservatively. Risk of bias was high in most studies, and all but three studies had a low level of evidence. For randomized studies, pooled event rates were 15 (95 per cent c.i. 10 to 22) per cent for the need for emergency intervention and 10 (5 to 20) per cent for recurrence of ACC. The pooled event rate for both outcomes combined was 20 (13 to 30) per cent. Conclusion: Antibiotics are not indicated for the conservative management of ACC or in patients scheduled for cholecystectomy. Abstract : Antibiotics not indicated